SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA RIMBA PETSHOP BANGKO JAMBI: Application, Information System, Marketing, Petshop, System - Afrizal, Afrizal; Louis, Ahmad; Ilahi, Taufiq (FORTECH (Journal of Information Technology), 2025)
Rimba Petshop is a store that sells a variety of products, including pet food and dog food. It also sells a variety of pet supplies, including cages, vitamins, and animal soap, and offers pet grooming services. Rimba Petshop's sales and promotion systems are still conventional and do not utilize electronic media. The methodology used in this research includes field research, library research, and laboratory research. The design method used in developing the marketing information system application at Rimba Petshop Bangko Jambi is a structured design method, starting with a global context diagram and then expanding it to a more detailed form, namely a Data Flow Diagram. The system and database design for the marketing information system at Rimba Petshop Bangko Jambi utilizes a web programming language, comprising a design for components or visual and non-visual objects, along with a graphical interface for data input and visitor interfaces for the Rimba Petshop Bangko Jambi marketing information system.